2022
DOI: 10.1021/acsanm.2c01529
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Interactions and Charge-Transfer Dynamics for a Series of Yolk–Shell Nanocrystals: Implications for Photocatalysis

Abstract: In recent years, yolk−shell nanocrystals have become the spotlight of research worldwide because of the fascinating structural properties such as a permeable shell, an interior void space, and a movable yolk. Numerous studies have reported various compositions of yolk−shell nanocrystals. Among them, yolk−shell nanocrystals comprising metal yolk and semiconductor shells are particularly interesting because they can be geared to mass transport-related utilizations, for example, photocatalysis. We reported a sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…This degradation indicated the existence of charge transfer interactions between the excited singlet state of P3HT and 4CzIPN or 2CzPN. 44 AFM and EDS analyses were performed to observe the morphological property. From the AFM images, the root mean square (rms) roughness of P3HT, P3HT:4CzIPN, and P3HT:2CzPN films are 0.646, 1.22, and 0.969 nm, respectively, suggesting a flat surface (Figure 2d−f).…”
Section: Results and Disscussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This degradation indicated the existence of charge transfer interactions between the excited singlet state of P3HT and 4CzIPN or 2CzPN. 44 AFM and EDS analyses were performed to observe the morphological property. From the AFM images, the root mean square (rms) roughness of P3HT, P3HT:4CzIPN, and P3HT:2CzPN films are 0.646, 1.22, and 0.969 nm, respectively, suggesting a flat surface (Figure 2d−f).…”
Section: Results and Disscussionmentioning
confidence: 99%
“…From the PL spectra, P3HT shows strong fluorescence with an emission peak at 580 nm, while the peak intensities of both P3HT:4CzIPN and P3HT:2CzPN decrease significantly and that of P3HT:2CzPN deteriorated more seriously (Figure c). This degradation indicated the existence of charge transfer interactions between the excited singlet state of P3HT and 4CzIPN or 2CzPN …”
Section: Results and Disscussionmentioning
confidence: 99%
“…This outcome can be realized by the diffusivity difference between the inward diffused S 2− ion, which is slower, and the outward diffused Cu + ion, which is faster. [ 36 ] Such a diffusivity difference caused a remarkable structural evolution from a solid, dense Cu 2 O shell for the starting Au@Cu 2 O into a hollow, permeable Cu 7 S 4 shell for the resultant Au@Cu 7 S 4 . The thus‐obtained Au@Cu 7 S 4 was characteristic of a mobile Au yolk and a permeable Cu 7 S 4 shell with an interior void space.…”
Section: Resultsmentioning
confidence: 99%
“…By sulfidation and kinetically controlled CER in Au/Cu 2 O core/shell NC template, four different yolk–shell NCs such as Au@Cu 7 S 4 , Au@ZnS, Au@CdS, and Au@Ni 3 S 4 were produced. [ 61 ] The X‐ray photoelectron spectroscopy (XPS) and PL spectroscopy results showed that there is pronounced charge carrier separation due to the interfacial charge transfer between the semiconductor shell and yolk, making them suitable for photocatalytic applications. The photocorrosion stability issues observed in CdS/Cu 2− x S heterostructure can be improved by fabricating stratified CdS–Cu 2− x S/MoS 2 heterostructures (Figure 10B(a,b)).…”
Section: Applications Of Heterostructured Ncsmentioning
confidence: 99%